This I Believe - Hamilton, Mary Agnes (Tufts Archival Research Center, 2006)
Mary Agnes Hamilton describes her belief in the soul and the bond it creates between fellow human beings, and her belief in absolute values that remain true despite the evils of Nazism and Communism.